Harmonic Interaction Analysis of Inverters Based on Harmonic State-Space Model Considering Dead-Zone Effect - Li, Shangshang; Wang, Shiyu; Mao, Yuxuan (International Journal of Mechanical and Electrical Engineering, 2024)
In the context of increasing device switching frequencies year by year, non-ideal factors such as dead-zone effects in inverters not only cause output waveform distortion, but also generate harmonics that make the interaction between inverters and power grids more complex. In order to accurately describe and analyze this phenomenon and establish a more practical grid-connected inverter model, this paper proposes and establishes a three-phase LCL grid-connected inverter harmonic state space model that considers dead-zone effects. By incorporating dead-zone effects into the modeling process, the system transfer function matrix is derived to quantify the harmonic interaction coefficient between the inverter and the power grid, and the influence mechanism of dead-zone effects on the harmonic interaction process at high switching frequencies is analyzed in depth. The necessity of considering dead-zone effects is illustrated through simulation, and the effectiveness and accuracy of the inverter HSS model considering the effects of dead-zone effects are verified through experiments.